2017
DOI: 10.1002/2017gl074515
|View full text |Cite
|
Sign up to set email alerts
|

Is El Niño really changing?

Abstract: El Niño–Southern Oscillation (ENSO) is the leading mode of tropical Pacific climate variability, with global impacts. Understanding how the statistics of ENSO events may be changing in response to global warming is of great interest and importance for society. A clear detection of such signals in observations has, however, been obscured by large event‐to‐event differences and apparent “regime shifts” such as that of the late 1970s. In particular, despite extensive research, it is not clear to what extent the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 33 publications
9
49
1
Order By: Relevance
“…We examined changes in ENSO variability in the Tropical Pacific, by quantitatively characterizing shifts in the statistics of SST and zonal wind. While previous studies have reported ENSO regime shifts based on either the second moment of SST or the Bjerknes stability index (Capotondi & Sardeshmukh, 2017;Hu et al, 2013;Lübbecke & McPhaden, 2014;McPhaden, 2012), we show the existence of strong contrast in higher-order moments' statistics between 1982-1999 (P1) and 2000-2014 (P2) for both winds and SST. In P1, for warm events, we see strong bimodality in SST in the NINO3 histogram, which is likely linked to nonlinear effects from the wind stress.…”
Section: Discussioncontrasting
confidence: 85%
“…We examined changes in ENSO variability in the Tropical Pacific, by quantitatively characterizing shifts in the statistics of SST and zonal wind. While previous studies have reported ENSO regime shifts based on either the second moment of SST or the Bjerknes stability index (Capotondi & Sardeshmukh, 2017;Hu et al, 2013;Lübbecke & McPhaden, 2014;McPhaden, 2012), we show the existence of strong contrast in higher-order moments' statistics between 1982-1999 (P1) and 2000-2014 (P2) for both winds and SST. In P1, for warm events, we see strong bimodality in SST in the NINO3 histogram, which is likely linked to nonlinear effects from the wind stress.…”
Section: Discussioncontrasting
confidence: 85%
“…In the EARS, extreme drought and rainfall events, which are already a characteristic feature of tropical climatology e.g. linked to ENSO or IOD [34,35], are widely believed to be changing in magnitude and/or frequency with global climate change [36]. In this context, we selected the Lake Manyara catchment system in Tanzania (figure 2) to represent a natural 'socio-ecological laboratory' typical of EARS catchments supporting vulnerable pastoral and agricultural communities in East Africa.…”
Section: Study Area: Lake Manyara Basin Northern Tanzaniamentioning
confidence: 99%
“…Studies indicate that the frequency, duration, and strength of ENSO vary from decade to decade (Enfield 1988;Trenberth andHoar 1996: Rajagopalan andCook 2000;Yuan et al 2009;Hu et al 2013;McGregor et al 2013;Cai et al 2014;Latif et al 2015;Wittenberg 2015;Räsänen et al 2016;Wang et al 2017;Capotondi and Sardeshmukh 2017;Li et al 2019). Recently, there has been debate over whether ENSO events are becoming more frequent and intense (Lee and McPhaden 2010;Newman et al 2011;Stevenson, 2012;Cai et al 2014).…”
Section: Introductionmentioning
confidence: 99%